Effective local control of advanced soft tissue sarcoma with neoadjuvant chemoradiotherapy and surgery: A single institutional experience - Stubbe, Franziska; Agaimy, Abbas; Ott, O.; Lettmaier, S.; Vassos, N.; Croner, R.; Hohenberger, Werner; Fietkau, Rainer; Semrau, S. (Cancer Radiotherapie, 2016)
There is a sound theoretical basis but little clinical evidence substantiating the benefits of concurrent chemoradiotherapy with two-drug chemotherapy for locally advanced soft tissue sarcomas. Our five-year data on the feasibility and effectiveness of neoadjuvant chemoradiotherapy with systemically effective doses of adriamycin and ifosfamide combined is presented here.Between 2000 and 2011, 53 patients with UICC (2010) stage I (n=1, 1.9%), II (n=12, 22.7%) or III (n=40, 75.5%) nonmetastatic soft tissue sarcoma received neoadjuvant chemoradiotherapy with ifosfamide (1.5g/m(2)/day, d1-5, q28) and doxorubicin (50mg/m(2)/day, d3, q28) plus concurrent radiotherapy with a target dose of 50-64Gy (median 60Gy). The treatment of 34 patients (64.2%) was combined with hyperthermia.At five years, the local control rate was 89.9% (±5.7%), distant metastasis-free survival 66.6% (±7.6%), and survival 83.3% (±6%). The R0 resection rate was 81.1%. Radiotherapy was completed as planned in all patients and chemotherapy in 42/53 (70.2%). Grades III (n=21, 29.6%) and IV (n=18, 34%) leukopenia was the main acute adverse event. All acute and chronic non-hematologic toxicities were moderate.Neoadjuvant chemoradiotherapy for soft tissue sarcoma is associated with good feasibility, manageable acute and late toxicities, and high local efficacy.
EVALuna2:6741